Cloud Gaming Masa Depan Industri Game - Dodick Zulaimi Sudirman (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2013)
With a high rate of internet penetration, many developer kept trying to innovate using Internet as the backbone. One innovation that is under a microscope of every technology observer is Cloud Gaming. In order to play a new game, player need to check their computer specification before even try to install the game. loud Gaming can solve that solution by using internet connection. Unfortunately Indonesia does not have a supporting infratructure in order to fully support Cloud Gaming. Index Terms—cloud gaming, video game, server architectire, software development, game industry